A Novel Method for Rapid and High-Performance SERS Substrate Fabrication by Combination of Cold Plasma and Laser Treatment - Thi Quynh Xuan Le; Thanh Binh Pham; Van Chuc Nguyen; Minh Thu Nguyen; Thu Loan Nguyen; Nguyen Thuan Dao (Nanomaterials)
In this paper, we report a simple yet efficient method for rapid and high-performance SERS substrate fabrication by a combination of cold plasma and laser treatment. Our analysis reveals that cold plasma pre-treatment significantly reduced surface roughness, transforming 200 nm spikes into an almost perfectly uniform surface, while enhancing the substrate’s surface energy by lowering the water contact angle from 59° to 0°, all achieved within just 30 s of 0.9-mW plasma treatment, while 15-min green-laser treatment facilitated more uniform deposition of AuNPs across the entire treated area, effectively creating the SERS substrates. The combined treatments result in enhancement of the Raman intensity (11 times) and consistency over the whole area of the SERS substrates, and their reusability (up to 10 times). The fabricated SERS substrates exhibit a significant enhancement factor of approximately 3 × 10⁸ with R6G, allowing detection down to a concentration of 10−12 M. We demonstrate the application of these SERS substrates by detecting amoxicillin—an antibiotic used worldwide to treat a diversity of bacterial infections—in a dynamic expanded linear range of seven orders (from 10−3 to 10−9 M) with high reliability (R2 = 0.98), and a detection limit of 9 × 10−10 M. Our approach to high-performance SERS substrate fabrication holds potential for further expansion to other metallic NPs like Ag, or magnetic NPs (Fe3O4).